Challenges of using natural gas as a carbon mitigation option in China. (June 2018) - Qin, Yue; Tong, Fan; Yang, Guang; Mauzerall, Denise L.
Abstract: Under the Paris Agreement, China committed to peak its carbon dioxide emissions on or before 2030. Substituting natural gas for coal may facilitate it meeting this commitment. However, three major challenges may obstruct progress towards desired climate benefits from natural gas. 1) A fundamental price dilemma dis-incentivizing a coal-to-gas end-use energy transition: low city-gate gas prices discourage an increase in gas supplies while high end-use gas prices impede an increase in gas demand. 2) Insufficient and constrained access to natural gas infrastructure hinders connections between gas supplies and end-users, and obstructs a balance in seasonal supply and demand. 3) Methane leakage from the natural gas industry compromises the direct greenhouse gas emission reductions from combustion. To address these challenges, government and industry must work together to facilitate natural gas market reform, increase investment in natural gas infrastructure, and control methane emissions. Highlights: Challenges exist in using natural gas as a carbon mitigation option in China. A fundamental price dilemma exists in China's natural gas market. Insufficient and constrained access to natural gas pipelines hinders gas market development. Gas storage investment is critical to balance seasonal gas supply and demand. Minimizing methane leakage is necessary to ensure net carbon mitigations.